The Analysis of Politeness Strategies in Directive Utterance as Found Among English Department Students at Dharma Andalas University - Widya Fhitri; Yalmiadi Yalmiadi (Fakultas Sastra Universitas Ekasakti, 2022)
This research describe and explain the indicators of politeness among students of English Department in Dharma Andalas University. This research uses descriptive qualitative analysis. The data of this research are the speech between English Department students. Retrieval of data using the refer method. This method is followed by a free and interactive technique. Data was collected by taking recorded conversations between students of English Department at Dharma Andalas University. The results of the research data show 5 indicators that students apply in their utterances, they are: the use of word help, sorry, greeting, could, and thank you. The use of greeting is the most indicator that the students used in their utterances, followed by the use of word help, could, sorry and the last one is 4 data of indicator that uses of word thank you.